Digitalizing Faraidh: A Netnographic Study of Islamic Inheritance Applications in Indonesia - Muhammad Fahmi Saifullah; Muhammad Rayhandi Isral (Jurnal El-Thawalib, 2026)
Digital transformation has reshaped Islamic religious practices, including the digitalization of Islamic inheritance law through mobile applications. Existing studies focus on technical development and quantitative user acceptance, neglecting users' interpretive practices, religious evaluations, and socio-cultural meanings in digital interactions. This study analyzes user experiences and perceptions of Islamic inheritance applications in Indonesia to understand how digital technology shapes and is shaped by Muslim users' religious practices. Employing netnography, this qualitative study examines 679 user reviews from eight Islamic inheritance applications on Google Play Store, scraped via Python on January 11, 2026. Analysis involved mapping application features into digitalization approaches, classifying reviews by sentiment, conducting thematic analysis, and examining fiqh-specific critiques to assess religious authority dynamics. Three digitalization approaches were identified: calculator-focused, educational, and multi-madhhab platforms. Positive themes included ease of use (29%), educational value (26%), fiqh accuracy (21%), methodological transparency (14%), and spiritual significance (10%), while negative dimensions covered fiqh errors (36%), feature limitations (24%), technical issues (17%), interface problems (11%), and monetization concerns (12%). Users demonstrate critical digital-religious literacy, evaluating applications against traditional religious authority rather than treating them as autonomous replacements, positioning these applications as mediators for informed negotiation at the intersection of technology, religious knowledge, and cultural values.